2017
DOI: 10.1080/13696998.2017.1360312
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of G5 Mobile continuous glucose monitoring device compared to self-monitoring of blood glucose alone for people with type 1 diabetes from the Canadian societal perspective

Abstract: The results of this analysis demonstrate that G5 Mobile CGM is cost-effective within the population of adults with T1DM using MDI, assuming a Canadian willingness-to-pay threshold of $50,000 CAD per QALY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…The majority use validated models, such as the Center for Outcomes Research (CORE) Diabetes Model 17 (a combination of Markov structure and Monte Carlo simulation), to simulate disease progression for a cohort of patients typically drawn from clinical trials or meta-analyses; however, results vary widely, likely due to differences in methodology. 18-22 Other concerns regarding much of the published cost-effectiveness research are estimation of costs over a long follow-up period (eg, 30 years to lifetime) and inclusion of both direct and indirect costs, both of which may limit the utility of the findings for payers. 23…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority use validated models, such as the Center for Outcomes Research (CORE) Diabetes Model 17 (a combination of Markov structure and Monte Carlo simulation), to simulate disease progression for a cohort of patients typically drawn from clinical trials or meta-analyses; however, results vary widely, likely due to differences in methodology. 18-22 Other concerns regarding much of the published cost-effectiveness research are estimation of costs over a long follow-up period (eg, 30 years to lifetime) and inclusion of both direct and indirect costs, both of which may limit the utility of the findings for payers. 23…”
mentioning
confidence: 99%
“…Most of the modeling studies examined the cost-effectiveness of standalone rtCGM versus SMBG in patients with T1DM and reported incremental cost-effectiveness ratios (ICERs) ranging from $33 789 per quality-adjusted life-year (QALY) gained to $98 679 per QALY. 18-20 In contrast, when modeling the cost-effectiveness of rtCGM in patients with T2DM, Fonda et al reported an ICER of $13 030 per QALY, and a modeling study by Roze et al, which focused on patients using an insulin pump in conjunction with rtCGM, reported an ICER of $54 698 per QALY. 21,22 A somewhat different type of modeling study used data derived from previously published research to determine the cost-effectiveness of standalone rtCGM in terms of decreasing the rate of severe hypoglycemia and subsequent hospitalization in adults with T1DM.…”
mentioning
confidence: 99%
“…Two of four studies reported that CGM and MDI were cost-effective when compared to SMBG and MDI. When adjusted for inflation, ICERs for CGM and MDI ranged from $37,470 AUD ($26, 361 USD) per QALY gained in the Canadian setting [31] through to $1,224,807 AUD ($861,686 USD) per QALY reported by Health Quality Ontario [32]. When insulin delivery comprised either CSII or MDI, four of five economic evaluations favoured CGM over SMBG, and ICERs ranged from $79,161 AUD ($55,692 USD) per QALY gained in the USA [16] through to $4,261,481 AUD ($2,997,832 USD) per QALY in Spain [33].…”
Section: Resultsmentioning
confidence: 99%
“…41 The disease burden of diabetes in 2015 (latest figure) was given a weight factor of 0.177, 42 which places it in the lowest category 43 of a maximum additional cost of up to €20.000/QALY to be considered for inclusion in the basic insurance package (Zorginstituut Nederland 2018). The study by VanGenugten (2010) of CGM cost-effectiveness in the Netherlands places it only slightly above the maximum willingness to pay threshold (+ €1731), as would the estimate from the Canadian study (+ €2858) by Chaugule and Graham (2017). The estimates from the Swedish and U.K. studies place the additional cost per QALY well below the maximum additional cost threshold (− €5590 and − €5721, respectively).…”
Section: Current Policy: the Case Of The Netherlandsmentioning
confidence: 95%